2008
DOI: 10.1097/maj.0b013e318180f21c
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Hurricane Katrina, Post-traumatic Stress Disorder and Birth Outcomes

Abstract: Background-Little is known about the effects of natural disasters on pregnancy outcomes. We studied mental health and birth outcomes among women exposed to Hurricane Katrina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
153
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(157 citation statements)
references
References 18 publications
1
153
1
2
Order By: Relevance
“…Term infants born to women who were pregnant on September 11, 2001 and who were living within a 2-mile radius of the WTC showed significant decrements in birth weight and body length at birth. In accord with these results, Xiong et al (2008) also reported three times higher rates of low birth weight in full-term infants when mothers were exposed to the Hurricane "Katrina." Besides these extremely negative life events, other authors have reported associations between maternal mental distress and lower birth weight.…”
Section: Introductionsupporting
confidence: 75%
“…Term infants born to women who were pregnant on September 11, 2001 and who were living within a 2-mile radius of the WTC showed significant decrements in birth weight and body length at birth. In accord with these results, Xiong et al (2008) also reported three times higher rates of low birth weight in full-term infants when mothers were exposed to the Hurricane "Katrina." Besides these extremely negative life events, other authors have reported associations between maternal mental distress and lower birth weight.…”
Section: Introductionsupporting
confidence: 75%
“…Specific high exposure to Katrina and the intensity of the experience was associated with low birth weight babies [3,43].…”
Section: Introductionmentioning
confidence: 99%
“…Sexual violence can lead to a rise of sexually transmitted diseases and injuries. Mental health issues, both acutely and chronic posttraumatic stress disorders, impacts the health and welfare of women and their families [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, the literature on disasters indicates limited effects on birth outcomes. Several studies of terrorist attacks 4 -9) , nuclear reactor accidents 10 -16) , and natural disasters (earthquakes 17 -20) and hurricanes 21,22) ) have been identified. Disasters of various types may affect on fetal growth, although there is no clear causal link to shortened gestation or preterm birth 3) .…”
Section: Introductionmentioning
confidence: 99%